2018
DOI: 10.1016/j.jcis.2018.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental impact of silica nanoparticles on the nanomechanical properties of Escherichia coli, studied by AFM

Abstract: Despite great innovative and technological promises, nanoparticles (NPs) can ultimately exert an antibacterial activity by affecting the cell envelope integrity. This envelope, by conferring the cell its rigidity and protection, is intimately related to the mechanical behavior of the bacterial surface. Depending on their size, surface chemistry, shape, NPs can induce damages to the cell morphology and structure among others, and are therefore expected to alter the overall mechanical properties of bacteria. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 84 publications
6
31
0
Order By: Relevance
“…For WT cells, analysis of the curves using the Hertz model ( Fig. 5b, d) yielded E of 3.5 ± 1.6 MPa (mean ± SD, n = 15 cells), in agreement with previously published values ranging from 1 to few MPa on E. coli [22][23][24] . The k b values were found to be 0.02 ± 0.01 N m −1 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…For WT cells, analysis of the curves using the Hertz model ( Fig. 5b, d) yielded E of 3.5 ± 1.6 MPa (mean ± SD, n = 15 cells), in agreement with previously published values ranging from 1 to few MPa on E. coli [22][23][24] . The k b values were found to be 0.02 ± 0.01 N m −1 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Ag NPs are well known for their antibacterial effects . Recent studies also reported silica particles, SWCNTs, and fullerene for antibacterial activity. The majority of antibacterial lignin materials make use of Ag ions or Ag NPs, as active payload.…”
Section: Effects Of Nano‐ and Microsized Lignins On Living Organismsmentioning
confidence: 99%
“…This equation further approximates the sample as a linear elastic and isotropic material, which is an obvious and well-recognized approximation for bacterial cell envelopes. 57 For the lack of better, this model is however widely used in AFM literature, and our purpose is here to test its applicability for capturing or not the power-law indentation-dependence of forces measured by PeakForce tapping mode on bacteria. Given these elements, eqn (1) may be rewritten in terms of the contact point CP (eqn (6)):…”
Section: Non-linear Deformation Models and Corrections For Nite Thicmentioning
confidence: 99%